Integration of Russia into theWorld Economy and Globalization of StockMarkets - A. K. Ivanov-Schitz (MGIMO University Press, 2009)
Correlations between Russian and some world leading stock market indices were analyzed to assess a degree of global integration of Russian economy. For this purpose, a new method of time-shift asymmetric correlation analysis was used. The method helps identify which stock market sets the pace and which one follows the lead. The analysis showed a growing trend in global integration of Russian economy. Particularly, it was shown that Russian stock market is getting more correlated with the European stock market while the leading (pace making) role of the U.S. markets keeps growing in the recession of 2008.